A simple spectrophotometric method for determination of thiamine (vitamin B1) in pharmaceuticals - Al-Ahmary, Khairia Mohammed (European Journal of Chemistry, 2014)
A simple spectrophotometric method has been described for the determination of thiamine. The method is based on the precipitation of sulphur as barium sulphate using barium chloride after oxidation of thiamine by sodium hydroxide and hydrogen peroxide. Beer's law was obeyed over the concentration range from 2-32 µg/mL thiamine. The average of standard deviation was 1.18×10-2; standard error, 5.20×10-3; relative standard deviation, 0.51%; relative standard error, 5.40×10-3; 95% coefficient, 1.48×10-2; the limit of detection, 0.41 µg/mL; the limit of quantification, 1.38 µg/mL and recovery, 100.03% thiamine. Finally, the developed method was applied to the determination of thiamine in pharmaceutical formulations.